Assessment of mandibular kinematics values and its relevance for the diagnosis of temporomandibular joint disorders - Oliver Leissner; Miguel Maulén-Yáñez; Walther Meeder-Bella; Camilo León-Morales; Eduardo Vergara-Bruna; Wilfredo Alejandro González-Arriagada (Elsevier, 2021)
Background/purpose: Temporomandibular disorders (TMD) are common conditions that involve the temporomandibular joints (TMJs), jaw muscles, or both, and can cause alteration in the mandibular kinematics. The aim of this study was to assess the relationship between mandibular kinematics and temporomandibular joint disorders (TMJD) as a clinical tool for evaluation and diagnosis of these patients. Materials and methods: A retrospective study based on the analysis of the clinical findings from patients' charts was carried out, with a sample size of 476 patients. Statistical analysis was made with chi-square test for qualitative variables and student t-test for quantitative variables. Then, odds ratio with its confidence interval were calculated. A p value < 0.05 was considered statistically significant. Results: Most patients were female (80.7%) and between 16 and 25 years old. Disc displacement with reduction (DDwR) and subluxation were associated with increased kinematic parameters, while disc displacement without reduction (DDwoR) and retrodiscitis were associated with decreased kinematic values. A soft end feel was related to osteoarthritis (OA). Structural incompatibility was most prevalent in older patients. Conclusion: Mandibular kinematic values are associated with specific temporomandibular joint disorders and could be considered as a useful clinical tool to perform the right diagnosis of TMJD.